A COMPARATIVE STUDY OF SEMANTIC DISTINCTION BETWEEN PAKISTANI ENGLISH AND BRITISH ENGLISH (Contemporary Journal of Social Science Review, 2025)
Semantics is a level of language that, like other levels, also changes. Semantic change can occur within a language or between languages. This paper examines the semantic changes in two language varieties resulting from the influence of local cultures. Pakistani English (PE) and British English (BE) have semantic distinctions in connotative meanings of various words. Onomasiological and semasiological mechanisms also support the extended and narrow changes in meaning. This is qualitative research, where data is collected from TV advertisements and Sunday magazines that discuss various aspects of life. The data is analyzed through the Pakistani corpus and the BNC (British National Corpus). The findings reveal that several words from British English have been adopted in Pakistani English, with generalized and extended meanings, and these new concepts are associated with words that reflect the local culture. The research is significant as it highlights the ways through which social contexts shape semantic change in Pakistani English